The fiddle of using the Paralympic Games as a vehicle for expanding [dis]ability sport participation - Howe, P. D.; Silva, C. F. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
In this paper, we highlight the need to explore the excessive significance given to the Paralympic Games as a vehicle for the encouragement of participation of people with a disability within sport. The media spectacle around the games that the International Paralympic Committee (IPC) has worked tirelessly to develop has become, for policy-makers and the public alike, a sufficient outlet for disability sport provision. The honourable goals of the IPC articulated through the ethos of Paralympism have been assumed to be valid for all people with a disability, yet in terms of widening participation, their utility is limited. This paper first illuminates the relationship between the International Olympic Committee and the IPC before we turn our attention to the ethos of Paralympism. Highlighting the necessity for `sport for all`, we use a human rights lens, aided by a capabilities approach to facilitate better ways to educate the public about the need for equality of access to sporting participation opportunities.